Patient selection considerations for AADC deficiency gene therapy - Agathe Roubertie; Irina Anselm; Bruria Ben‐Zeev; Wuh‐Liang Hwu; Ashutosh Kumar; Berrin Monteleone; Shin‐ichi Muramatsu; Vincenzo Leuzzi; Salvador Ibáñez; Scellig Stone; Phillip L. Pearl (Wiley, 2024)
Abstract Background Aromatic ʟ‐amino acid decarboxylase (AADC) deficiency is a rare, severe neurological disorder caused by pathogenic variants in the dopa decarboxylase (DDC) gene, resulting in a combined deficiency of monoamine neurotransmitters. Clinically, patients present with a range of dysfunctions that impact motor, autonomic, and cognitive development. The constellation of symptoms of AADC deficiency varies among patients, and clinical presentation falls across a wide spectrum. However, most patients with AADC deficiency experience significant impairments when compared with children with normal development, irrespective of genotype, phenotype, or disease severity. Further, AADC deficiency is associated with increased mortality. Methods In response to the recent approval of a disease‐modifying gene therapy for AADC deficiency, this review presents considerations for the selection of patients for treatment. Conclusion Suggested clinical criteria to determine whether a patient is a candidate for gene therapy are: (1) genetically and biochemically confirmed AADC deficiency; (2) lack of achievement of gross motor milestones and/or persistence of clinically significant movement disorders; (3) persistent neurocognitive or systemic symptoms secondary to AADC deficiency despite standard medical therapy; and (4) informed parental/guardian decision and consent to treatment.